2003
DOI: 10.4049/jimmunol.171.2.547
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Germinal Centers Formed in the Absence of B Cell-Activating Factor Belonging to the TNF Family Exhibit Impaired Maturation and Function

Abstract: Germinal centers (GCs) form in B cell follicles and require specific signals for development and maintenance. B cell-activating factor belonging to the TNF family (BAFF) is a fundamental B cell survival factor and therefore may influence GC reactions and subsequent Ab responses. To test this possibility, the effect of BAFF neutralization in immunized mice was assessed. Using B cell maturation Ag-Fc, we demonstrate that BAFF blockade does not inhibit GC formation or somatic hypermutation. However, GCs in B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
97
0
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 25 publications
11
97
0
12
Order By: Relevance
“…Furthermore, WT mice treated with a BAFF inhibitor produce high-affinity Ab, although the quantity is diminished (16,17). Recently we showed that BAFF KO and BCMA-Fc-treated WT mice form GCs with intact somatic hypermutation (7). Together, these data suggest the existence of mature B cells in BAFF KO mice.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, WT mice treated with a BAFF inhibitor produce high-affinity Ab, although the quantity is diminished (16,17). Recently we showed that BAFF KO and BCMA-Fc-treated WT mice form GCs with intact somatic hypermutation (7). Together, these data suggest the existence of mature B cells in BAFF KO mice.…”
Section: Discussionmentioning
confidence: 53%
“…However, it was shown that while the humoral responses to T-dependent Ags were severely impaired in BAFF KO mice, Ag-specific, classswitched Ab was still produced (2,3). Recently, we showed that BAFF KO mice form germinal centers (GC) with intact somatic hypermutation after Ag challenge (7). These findings suggest that BAFF KO mice possess more differentiated, mature B cells than originally believed.…”
mentioning
confidence: 76%
“…The B cell growth and survival factors BAFF (B cell activation factor of the TNF family) and APRIL (A proliferation-inducing ligand) also contribute to the establishment of FDC networks and GC-reactions in SLO as well as in RA synovitis (39,40). One of their receptors, TACI (soluble transmembrane activator and calcium modulator and cyclophilin ligand-interactor), negatively regulates this process (41,42).…”
Section: Increased Baff and Taci Expression In Ra Synovitismentioning
confidence: 99%
“…Furthermore, preliminary gene expression experiments using DNA microarrays indicate that as compared to other naïve B cells that regularly participate in productive GC reactions, 9G4 naïve cells express decreased levels of NF-κB and JNK kinase, a profile characteristic of anergic autoreactive transgenic B cells [91,92]. Several mechanisms could be postulated to explain the failure of pre-GC 9G4 B cells to successfully participate in a mature GC reaction including defective responses to stimulation through the BAFF receptor [93,94]. In addition, when stimulated in the presence of surrogate T cell help, healthy naïve 9G4 B cells readily differentiate into antibody-producing plasma cells (PC), thereby suggesting that their inability to do so in vivo may be due, at least in part, to the absence of T cell help, a mechanism known to contribute to the maintenance of tolerance in transgenic anti-DNA B cells [15,95].…”
Section: Autoreactive 9g4 B Cells Are Censored In a Healthy Immune Symentioning
confidence: 99%